Evaluations on efficacy and immuno-stimulatory properties Tropomyosin receptor kinase C targeted peptidomimetic ligand-diiodo-boron dipyrromethene hybrids in photodynamic anticancer therapy / Kue Chin Siang - Kue, Chin Siang (2016)
Photodynamic therapy (PDT) utilises the administration of photosensitiser (PS) along with focal light activation at specific wavelengths to generate singlet oxygen species to kill tumour cells. Currently, most of the available photosensitisers have poor tumour selectivity. This has led to poor therapeutic outcome. In order to improve the tumour selectivity of the PS, a Tropomyosin receptor kinase C (TrkC) receptor based active targeting ligand-PS complex was synthesised. TrkC is being targeted due to its overexpression in cancer including breast, melanoma, pancreatic, neuroblastoma etc. In this study, a synthetic isoleucine-tyrosine-isoleucine-tyrosine based TrkC receptor ligand (IY-IY) was linked to a model photosensitiser diiodo-boron dipyrromethene I2-BODIPY to form a TrkC targeting PS derivative IYIY-I2-BODIPY. Thereafter, tumour targeting properties, in vivo antitumour efficacy and immune stimulatory properties of conjugates in TrkC positive (4T1) and TrkC negative (67NR) breast cancer models in pre and post-PDT scenarios were evaluated. Data showed that IYIY-I2-BODIPY, but not a scrambled control (YIYI-I2-BODIPY) and free drug (I2-BODIPY) selectively induced photocytotoxicity in a dose-dependent manner in 4T1 cells upon irradiation. Bio-distribution studies in 4T1 mouse model showed that IYIY-I2-BODIPY accumulated high in tumours at 1 h post intravenous administration and maintained high up to 6 h, at a level which was approximately 2-fold higher compared to YIYI-I2-BODIPY. Antitumour activity of IYIY-I2-BODIPY in 4T1 showed 96% reduction in tumour volume at day-6 post PDT at 10 mg/kg. Moreover, 71% of IYIY-I2-BODIPY treated mice were “healed” from aggressive breast cancer for up to 90 days post-PDT with no evidence of metastasis, indicating complete remission. This observation was neither found in YIYI-I2-BODIPY nor I2-BODIPY treated mice. The selectivity of IYIY-I2-BODIPY was further confirmed when 67NR breast tumours in mice showed only slight tumour reduction followed by tumour re-growth upon PDT using all three compounds. At a similar therapeutic dosage, IYIY-I2-BODIPY (strong response) and YIYI-I2-BODIPY (weak response), but not I2-BODIPY, in non-irradiation condition selectively increases the pro-inflammatory cytokines IL-2, IL-6, IL-17 and suppresses immunosuppressive cytokines TGF-β at 2 h post administration. Moreover, the conjugates increase both CD4 and CD8 T-lymphocyte populations with phenotype of IFN-γ (Th1, CTL) and IL-17 (Th17, Tc17), and decreases immunosuppressive granulocytic myeloid-derived suppressor cells (G-MDSC) and regulatory T cells, which were known to be highly increased in cancer. Only IYIY-I2-BODIPY induced tumor growth delay (~20% smaller size) in mice when administrated daily for 5 days. When illuminated with light to produce effects associated with PDT, IYIY-I2-BODIPY induced even stronger immune responses. In addition, IYIY-I2-BODIPY and light treated mice had higher levels of immune effector T-cells compared to photoirradiated YIYI-I2-BODIPY and I2-BODIPY controls. Adoptive transfer of splenocytes and lymphocytes from IYIY-I2-BODIPY treated survivor mice that were photoirradiated gave significantly delayed tumour growth in recipient mice. Our data provide evidences that TrkC ligand conjugate, alone and in combination with PDT modulates immune responses that are conducive to suppressing tumour growth. Thus this conjugate can act as an immune-stimulatory PDT agent with potential applications in cancer treatment.